Waste Office Paper Derived Cellulose‐Based Carbon Host in Freestanding Cathodes for Lithium‐Sulfur Batteries. Issue 11 (13th June 2022) - Yan, Yinglin; Yang, Yuanyuan; Fan, Chaojiang; Zou, Yiming; Deng, Qijiu; Liu, Haidong; Brandell, Daniel; Yang, Rong; Xu, Yunhua
Abstract: Due to large sulfur (S) content and simple manufacturing techniques, free‐standing cathodes for lithium‐sulfur (Li−S) batteries are gaining a lot of attention recently. Waste office paper, which is consumed in large quantities annually, was used to make a free‐standing paper‐based carbon (FPC) substrate, which inherited fiber‐like morphology. In addition, reduced graphene oxide (rGO) nanosheets modified FPC (rGO@FPC) host was also prepared by a vacuum filtration method. After S impregnation, the FPC/S and rGO@FPC/S free‐standing cathodes were employed in Li−S batteries. The rGO@FPC/S free‐standing cathode exhibited extremely competitive electrochemical performance, including a reversible discharge capacity of 315 mAh g −1 at 0.5 C after 500 cycles. This is due to the uniform S distribution, which boosts the utilization ratio, and the significant blocking action for polysulfide ions, which prevents the redox shuttle effect. Abstract : From waste to battery : Waste office paper was used to prepare a free‐standing paper‐based carbon (FPC) substrate, which was further modified with reduced graphene oxide (rGO) nanosheets (rGO@FPC) by a vacuum filtration method. After S impregnation, the rGO@FPC/S free‐standing cathode was employed in Li−S batteries, which exhibited competitive cycling life and significant blocking action for polysulfide ions.